Physicochemical characterization and oxidative potential of size fractionated Particulate Matter: Uptake, genotoxicity and mutagenicity in V-79 cells - Kavita Dubey; Renuka Maurya; Durgesh Mourya; Alok Kumar Pandey (Ecotoxicology and Environmental Safety, 2022)
For many years, the impact of Particulate Matter (PM) in the ambient air has been one of the major concerns for the environment and human health. The consideration of the heterogeneity and complexity of different size fractions is notably important for the assessment of PM toxicological effects. The aim of the study was to present a comprehensive size-composition-morphology characterization and to assess the oxidative potential, genotoxicity, and mutagenicity of the atmospheric PM fractions, collected by using MOUDI near a busy roadside in Lucknow, India. Physicochemical characterization of ambient coarse particles (1.8–10 µm), fine particles (0.32–1.8 µm), quasi-ultrafine (0.1–0.32 µm) and ultrafine particles (≤0.1 µm) along with SRM 1649b was done using TEM, SEM, DLS, NTA, ICP-MS, and IC in parallel with the estimation of exogenous Reactive Oxygen Species (ROS) by acellular assays. In this study, two different acellular assays, dithiothreitol (DTT) and the CM-H2DCFDA assay, indicated stronger mass-normalized bioactivity for different size ranges. Enrichment factor analysis indicated that the different size fractions were highly enriched with elements of anthropogenic origin as compared to elements of crustal origin. The endotoxin concentration in different size fractions was also estimated. Cellular studies demonstrated significant uptake, cytotoxicity, ultrastructural changes, cellular ROS generation, and changes in the different phases of the cell cycle (Sub G1, G1, S, G2/M) exposed to different size fractions. The Comet assay and the Micronucleus assay were used to estimate genotoxicity. Mutagenic potential was revealed by the HGPRT gene forward mutation assay in V-97 cells. Conclusively, our results clearly indicate that the genotoxic and mutagenic potential of the coarse PM was greater than the other fractions, and interestingly, the ultrafine PM has higher bioactivity as compared to quasi-ultrafine PM.